Patriarchal Culture and the PKB Party's Strategy in Advocating for Female Candidates in the East Java Regional Election - Muhammad Norcahyo; Nur Addiansyah (Politeia: Jurnal Ilmu Politik, 2026)
This study aims to analyze the influence of patriarchal culture on the strategy of the National Awakening Party (PKB) in promoting women's involvement in political contestation, particularly in the Regional Head Elections (Pilkada) in East Java Province. Using a descriptive qualitative approach, this research provides an in-depth depiction of how patriarchal cultural structures affect the internal dynamics of the party and the strategies implemented to encourage women's participation. Data collection was conducted through literature studies, obtained from related research including journals, articles, and online news to support the analysis. The findings reveal that patriarchal culture has become both a cultural and structural barrier that limits women's political mobility, in both the nomination phase and the electoral process. PKB has responded to these challenges through various strategies, such as implementing gender quotas, conducting female cadre training, collaborating with women’s religious organizations, and strengthening gender-inclusive political communication. However, the implementation of these strategies has not yet been fully effective due to persistent cultural resistance at the local level, limited internal structural support, and public perceptions biased against female leadership. Therefore, there is a need for more systematic and sustainable strategic efforts to ensure that women’s political participation is not merely symbolic but genuinely reflects a transformative, inclusive, and equitable democracy at the local level